Urban Groundwater Processes and Anthropogenic Interactions (Porto Region, NW Portugal) - Afonso, Maria José (2021)
Groundwater in fissured rocks is one of the most important reserves of available fresh water, and urbanization applies an extremely complex pressure which puts this natural resource at risk. Two-thirds of Portugal is composed of fissured aquifers. In this context, the Porto urban region is the second biggest metropolitan area in mainland Portugal. In this study, a multidisciplinary approach was developed, using hydrogeological GIS-based mapping and modeling, combining hydrogeochemical, isotopic, and hydrodynamical data. In addition, an urban infiltration potential index (IPI-Urban) was outlined with the combination of several thematic layers. Hydrogeochemical signatures are mainly Cl-Na to Cl-SO4-Na, being dependent on the geographic proximity of this region to the ocean, and on anthropogenic and agricultural contamination processes, namely fertilizers, sewage, as well as animal and human wastes. Isotopic signatures characterize a meteoric origin for groundwater, with shallow flow paths and short residence times. Pumping tests revealed a semi- to confined system, with low long-term well capacities (<1 L/s), low transmissivities (<4 m2/day), and low storage coefficients (<10−2). The IPI-Urban index showed a low groundwater infiltration potential, which was enhanced by urban hydraulic and sanitation features. This study assessed the major hydrogeological processes and their dynamics, therefore, contributing to a better knowledge of sustainable urban groundwater systems in fractured media